2021
DOI: 10.51253/pafmj.v6i6.6338
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Progressive Muscular Relaxation (Pmr) and Music Therapy (Mt) in Reducing the Anxiety, Depression and Stress Symptoms Among Nurses

Abstract: Objective: To compare the progressive muscular relaxation and music therapy in reducing the anxiety, depression and stress symptoms among nurses. Study Design: Quasi-experimental Study. Place and Duration of Study: Various hospitals in Rawalpindi, from Mar 2018 to Mar 2019. Methodology: Sample of study was 20 female nurses. They were assessed by using depression, anxiety and stress scale (DASS21), Urdu version. Study participants were randomized into two groups, group 1= who received the musi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 13 publications
(13 reference statements)
0
6
0
Order By: Relevance
“…When delving deeper into individual outcome measures, for stress, one (1) study 59 found no significant reduction in stress level when compared to the control group at posttest. For anxiety, there are five (5) studies 34 , 49 , 51 , 79 , 81 reported no reduction in anxiety at the posttest. Interestingly, there are two (2) studies 42 , 50 that show a significant reduction of anxiety in the control group which calls for more research to uncover the underlying causes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…When delving deeper into individual outcome measures, for stress, one (1) study 59 found no significant reduction in stress level when compared to the control group at posttest. For anxiety, there are five (5) studies 34 , 49 , 51 , 79 , 81 reported no reduction in anxiety at the posttest. Interestingly, there are two (2) studies 42 , 50 that show a significant reduction of anxiety in the control group which calls for more research to uncover the underlying causes.…”
Section: Discussionmentioning
confidence: 99%
“…35 Anxiety There is a significant decrease (↓) in trait anxiety score in post-test compared to pretest in both IG and CG. High 13 Mustafa et al 51 (2021) Pakistan 4 sessions/ 4 weeks N/A 10 female nurses (PMR: 10) S: N/A DO: 0% QED / / DASS-21 N/A Stress (d=2.45), anxiety (d=0.53), depression (d=1.95) There is a significant decrease (↓) in stress and depression score but not in anxiety at post-test compared to pretest in IG. High 14 Palkar et al 52 (2021) India 45m at home/ 4 weeks + 3 sessions at seminar hall 7 days/ week 114 medical students (PMR: 43, CG: 71) S: Seminar Hall & at home DO: 0% QED / / PSS, TAS N/A Stress (d=0.45), Anxiety (d=0.35) There is a significant decrease (↓) in stress and anxiety score at post-test compared to pretest in IG.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations